Teatr i dramat ciągle w morderczym uścisku. Uwagi na marginesie książki Hansa-Thiesa Lehmanna pt. „Teatr postdramatyczny" - Maciąg, Rafał (Przestrzenie Teorii, 2008)
Article refers to Hans-Thies Lehmann ideas of understanding the drama shown in his book Postdramatic Theatre and tries to discuss with them. Lehmann shows synthetic theory of drama based on the thought coming from Georg Friedrich Hegel by the theory of modern drama of Peter Szondi, which interprets drama as the product of historical progress. Article expresses disappointment with several simplifications embedded in Lehmann theory of the constructing mechanisms of the presenting the real world phenomena used by the drama. Indicates the possibility of the different interpretation of the philosophic inspiration coming from Hegel and shows as an example proposition of Jacques Derrida. Article remains in the area of this analytic tradition and emphasizes semantic polyphony of the dramatic text, which i based on the special sense of time but completely different than Lehmann's is.